CS04 | Association between elevated plasma levels of tissue plasminogen activator (tPA) and occult cancer risk: a nested case-cohort analysis in 10,294 healthy subjects (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Tissue plasminogen activator (tPA), an enzyme involved in the fibrinolytic system, has been associated with cancer progression, but limited prospective data are available. Therefore, its role in predicting cancer risk is yet undefined. This study aimed to investigate whether circulating tPA levels predict cancer occurrence in a large cohort of healthy subjects, i.e. blood donors enrolled in the prospective HYPERCAN study (ClinicalTrials.gov ID#NCT02622815).